1975
DOI: 10.1007/bf02640736
|View full text |Cite
|
Sign up to set email alerts
|

Study on skin roughness caused by surfactants: I. A new method in vivo for evaluation of skin roughness

Abstract: A New ABSTRACTA simple and accurate method for evaluating skin roughness caused by surfactants has been developed. The intensities of the roughness have been correlated with the chemical structures of surfactants by using this method. Results indicated in general, that the surfaetants having 12 carbons in their alkyl chain gave the skin more roughness than did those which had more or less than 12. The results obtained by this method were in good agreement with those from the immersion method usually used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Surfactants can damage the skin, provoking scaling [1][2][3], perceived sensations of dryness, tightness and roughness [2][3][4][5][6], and extreme irritation marked by ery thema and swelling [7,8]. The mechanism(s) w'hcreby surfactants elicit these effects is not fully understood, it has been suggested that protein denaturation and inhibi tion of enzyme activity arc implicated in surfactant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants can damage the skin, provoking scaling [1][2][3], perceived sensations of dryness, tightness and roughness [2][3][4][5][6], and extreme irritation marked by ery thema and swelling [7,8]. The mechanism(s) w'hcreby surfactants elicit these effects is not fully understood, it has been suggested that protein denaturation and inhibi tion of enzyme activity arc implicated in surfactant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Alkyl sulfate (AS) (CnH2n+IOSO3Na[CnAS]), alkyl polyoxyethylene sulfate(ES) ( (1,(7)(8)(9)(10), with respect to alkyl distribution, ratios of the isomer of alkylbenzene sulfonate, and ratios of alkene and hydrox forms in alfa-olefin sulfonate. The list of surfactants is shown in Table I together with their alkyl distribution and purities.…”
Section: Surfactantsmentioning
confidence: 99%
“…Since wellknown removers of lipids, such as surfactants or organic solvents, induce dry skin (2)(3)(4) which is characterized specifically by reduced water content in the stratum corneum, it appears that the structural lipids may also play a considerable role in the water-holding potential of stratum corneum. Little is known, however, about the function of stratum corneum lipid in water-holding properties, despite that some evidences suggest a role for skin barrier function and stratum corneum cohesion (5,6).…”
mentioning
confidence: 99%